Analisis Kemampuan Literasi Informasi antara Anggota Ikatan Pustakawan Pelajar dan Non Anggota Pada Siswa SMAN 5 Malang Berdasarkan Model Empowering Eight - Azzarah, Marshanda Anta; Prasetyawan, Adi (Al-Mamun Jurnal Kajian Kepustakawanan dan Informasi, 2024)
Introduction. The focus of this research is to determine the comparison in the analysis of information literacy skills based on the empowering eight model, as an effort in information seeking to complete paper assignments. According to the author's belief, members of the student librarian association surely have a different frequency of library visits compared to non-member students because their tasks and functions are indirectly related to the library. Data Collection Methods. The research that will be conducted will use a quantitative method, with a descriptive mono-variable approach. Data Analysis. The primary data source is the main sample of the research obtained from the questionnaire. Secondary data acquisition involves the use of supporting literature and previous research. The sampling technique used in this study is quota sampling. The data analysis procedures involve validity testing (Pearson correlation), reliability testing (Cronbach's alpha), and descriptive statistical analysis. Results and Discussion. The results of this study indicate that there is a significant difference between the skill outcomes of students who are members of the DLC and those who are not. The main deficiency for both groups of students, whether DLC members or non-members, lies in determining the topic for paper composition. The weakness lies in the application of the empowering eight information literacy model to determine the topic. The strength of both groups of students lies in their ability to select information. Conclusion. There is a need to improve information literacy skills, particularly in identifying information for the purpose of determining paper topics. Libraries can provide training and workshops on information literacy to address this issue.